Pengurangan Kadar Ammonia dalam Limbah Cair Pupuk pada Jet Bubble Column Menggunakan NaOH - Adis Aisyah Amini; Indah Purnamasari; Erwana Dewi (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
As a developing country, Indonesia is experiencing continuous industrial growth, including the urea fertiliser industry. The presence of the urea fertilizer industry produces wastewater containing ammonia pollutants, a primary component in the manufacture of fertilizers. Wastewater containing ammonia is discharged into rivers, polluting the environment and affecting living organisms both directly and indirectly. The aim of this study is to reduce the ammonia levels in the fertiliser effluent and to monitor the effect of the added NaOH solvent using a Jet Bubble Column. The reduction of ammonia levels in the wastewater was carried out by adding 0.3 M NaOH solvent to 1 litre of wastewater at a liquid flow rate of 0.9 litre/minute with varying air flow rates of 8 litre/minute and 12 litre/minute and temperatures of 35°C, 40°C, 45°C, 50°C and 55°C over an operating time of 60 minutes. The samples were analysed using Nessler UV/Vis spectrophotometry at a wavelength of 460 nm, and the mass transfer coefficient (kLa) and efficiency of ammonia reduction by the Jet Bubble Column were calculated. The highest efficiency obtained was 68.75%, reducing 434.214 ppm in 60 minutes at an air flow rate of 12 litres/minute and a temperature of 55°C. Higher flow rates and temperatures resulted in greater reductions, with the highest kLa being 1,074.